Selection of Grass and Broadleaf Crops as Catch Crops where Winery Wastewater is Used for Irrigation: A Review - Fourie, J.C.; Howell, C.L.; Masekwana, N. (South African Journal of Enology and Viticulture, 2021)
Winery wastewater contains high levels of elements such as sodium, phosphorus, potassium, as well as chemical oxygen demand, sodium adsorption ratio and pH. This may raise concerns regarding the pollution of the surrounding environment. Environmentally friendly methods such as recycling, i.e. treatment and re-use, where treated or partially treated and diluted wastewater is used for irrigation of agricultural crops, are essential. Irrigation with winery wastewater, which is rich in nutrients, can be beneficial to overall soil fertility as an alternative to conventional fertilizers. However, long-term applications of wastewater may have a negative effect on soil physicochemical properties. A selection of crops with nutrient interception abilities, preferably for salts, may be ideal for the removal of excess elements from the soil whilst reducing leaching and excess run off. The use of perennial grasses, annual winter growing grains and winter growing broadleaf nitrogen-fixing annuals as winter cover crops in the South African wine industry has been extensively documented but their use as summer catch crops intercepting elements applied via wastewater irrigation has not yet been well researched.